Do bispo morto ao padre matador (Dom Expedito e Padre Hosana nas construções da memória – 1957/2004) - Moreira, Igor Alves (2008)
The present work is devoted to the historical study on the memoirs around Expedite Talent Lopes and priest Hosana of Siqueira and Silva. Expedite talent was bishop of Garanhuns-Pernambuco. In 1957, it was murdered by priest Hosana with three revolver shots. The crime generated narratives. He/she/you founded multiple memoirs. Those narrative plots give dinamicidade to the past. The concern is not simply to explain the a lot of memoirs on the crime, but to think as those memoirs was counted and recounted by the letters and for the speech of the depoentes that, as those memories, they built and they build senses that evidence specific papers of villainous (I murder) and hero (example). to Notice as the crime is narrated and your multiple variations are here the objective looked for.